Keys for architectural history research in the digital era : Handbook - Antonio Mendes da Silva (Publications de l'Institut national d'histoire de l'art, 2014)
This handbook gathers a selection of texts by the speakers at the Training School "Architectural Research in the Digital Era" (Ghent, 2-6 April 2013) and the workshop "GIS, data visualization an open community" (Paris, 27-28 January 2014). The aims of these two events organised in the framework of the COST ISO904 Action European architecture beyond Europe: Sharing Research and Knowledge on Dissemination Processes, Historical Data and Material Legacy (19th-20th centuries), was to familiarize the participants, architectural historians with a variety of aspects related to conducting research in a digital era: Architectural history research in the digital era Copyrights; Standards, metadata, interoperability and sustainability; Data visualisation; Creating a digital research environment, GIS and Open communities.